Case report: Two cases of pyloric adenomas with high-grade intraepithelial neoplasia at distinct locations - Li, Yuetian; Chen, Shuai; Zhao, Xuechun; Wang, Quanyi (Frontiers in Immunology, 2024)
The rare gastrointestinal tract epithelial polyp known as a pyloric gland adenoma (PGA) is more common in elderly women and uncommon in the duodenum. There are reports of two PGA cases involving high-grade intraepithelial neoplasia. A 75-year-old man was admitted to the hospital as Patient 1 due to “epigastric distension and pain for more than 10 days”. The mucous membrane around the stomach fundus and body was thin, and an electron gastroscopy revealed a large, thick protrusion in the stomach fundus that measured about 6 cm in circumference. High-grade intraepithelial neoplasia and stomach pyloric adenoma are the pathological diagnoses. An outside hospital provided consultation for Patient 2, a 68-year-old male. Pyloric adenoma at duodenal bulb with high-grade intraepithelial neoplasia is the pathological diagnosis. The single layer of cuboidal to low columnar epithelial cells with rounded nuclei and eosinophilic cytoplasm was surrounded by densely packed glands with sporadic cystic dilatation that made up the tumor tissue. The diagnosis of PGA required the immunohistochemical labeling of MUC6. In both cases, simple surgical resection was carried out, and followed up for half a year, no recurrence.